Analysis of Capital Structure Theory on Company's Funding Decisions - Wagisuwari, Kadek Saptaria; Sitorus, Palti M.T. (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
This study is meant to identify variables that should be considered while making funding decisions and identify the theory of the capital structure that is relevant in funding decisions. The study is conducted in property and real estate company listed in Indonesia Stock Exchange. This study is descriptive quantitative research using purposive sampling method and able to gather 70 observation data that would be processed by panel data regression analysis on Eviews. The results in trade-off theory show that debt tax shield and firm age perspective have positive impact on company's funding decision. In pecking order theory model, it is found that financial deficit has a positive effect while business risk is the opposite. Positive effect is also found on the proportion of independent commissioners, but growth opportunity variable is considered to be neutral and doesn't have effect on capital structure in agency theory.